2016
DOI: 10.1016/j.jmii.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Honey: A realistic antimicrobial for disorders of the skin

Abstract: Resistance of pathogenic microorganisms to antibiotics is a serious global health concern. In this review, research investigating the antimicrobial properties of honeys from around the world against skin relevant microbes is evaluated. A plethora of in vitro studies have revealed that honeys from all over the world have potent microbicidal activity against dermatologically important microbes. Moreover, in vitro studies have shown that honey can reduce microbial pathogenicity as well as reverse antimicrobial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 41 publications
0
59
0
2
Order By: Relevance
“…The compounds present in honey are carbohydrates (fructose), 18 free amino acids, water, calcium, iron, zinc, potassium, phosphorous, magnesium, selenium, chromium, manganese, proteins, enzymes, and vitamins such as vitamin B 2 , B 4 , B 5 , B 6 , B 11 , and vitamin C, which are essential elements for the production of erythrocytes . The used amounts range from 1% to 10%, but concentrations up to 70% can be achieved by mixing with oils, gel, and emulsifiers, or polymer entrapment in facial mask . Also, the new features of honey discovered by the recent studies are useful.…”
Section: Ingredients Of Facial Mask and Mechanisms Of Actionmentioning
confidence: 99%
“…The compounds present in honey are carbohydrates (fructose), 18 free amino acids, water, calcium, iron, zinc, potassium, phosphorous, magnesium, selenium, chromium, manganese, proteins, enzymes, and vitamins such as vitamin B 2 , B 4 , B 5 , B 6 , B 11 , and vitamin C, which are essential elements for the production of erythrocytes . The used amounts range from 1% to 10%, but concentrations up to 70% can be achieved by mixing with oils, gel, and emulsifiers, or polymer entrapment in facial mask . Also, the new features of honey discovered by the recent studies are useful.…”
Section: Ingredients Of Facial Mask and Mechanisms Of Actionmentioning
confidence: 99%
“…Entomotherapy is the use of insects as medicine and is an important alternative to modern therapy in many parts of the world including India, Mexico, Korea, China, Spain, Brazil, Argentina, Ecuador and various African countries today8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22. Honey, a sweet bee byproduct, is valued as an antioxidant and antimicrobial agent, suitable for the battle against heart disease and skin disorders23, 24, 25, 26, 27. Propolis, a gap filling “glue” used in the construction of the beehive, has been evaluated extensively for its potential antioxidant, antimicrobial, anti-inflammatory, cardioprotective, immunomodulatory and antiangiogenic properties28, 29, 30.…”
Section: Introductionmentioning
confidence: 99%
“…The skin healing properties of honey have been largely attributed to its anti-microbial properties; a plethora of in vitro studies have demonstrated antimicrobial activity of honeys from all over the world against dermatologically important microbes (Schneider, Coyle, Warnock, Gow & Fyfe, 2013;Kuncic, Jaklic, Lapanje & Gunde-Cimerman, 2012;McLoone, Warnock & Fyfe, 2015). More recently, in vitro research has suggested that honeys of diverse floral origins can modulate the skin immune system; both immunostimulatory and antiinflammatory effects have been observed (Majtan, Kumar, Majtan, Walls & Klaudiny, 2009;Majtan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%